Design and Characterization of Sustained Release in situ Gastric Floating Gel of Ropinirole Hydrochloride - Basu, Ananya; Masareddy, Rajashree Shashidhar; Patil, Archana; Bolmal, Uday (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: This in situ solution which on gelation floats in the gastric region is suitable for sustaining the release of the drug. In the present research work, Ropinirole Hydrochloride which is an Anti-parkinson agent, used to formulate an in situ gel for prolonged action. Materials and Methods: Sodium alginate is a natural polymer used to form the gel matrix, calcium carbonate plays a dual role i.e. the source of CO2 entrapped in the matrix for floatation of gel and source of Ca2+ ion for sol to gel transition, HPMC K100M as the release retard polymer was investigated. The mechanism for the floatation of the gel was pH induced ion gelation. For the formulated in situ solution different evaluation parameters were used. Results and Discussion: On the basis of the outcomes pale colored, viscous solution of uniform consistency was obtained, the drug content was found to be >87%, the viscosities were in the acceptable range suitable for swallowing, pH was found to be in the range of 7.35-7.87 which was compatible for oral ingestion. Design Expert 12 software was used to derive the results of interaction and responses on the basis of concentration of polymer and statistical analysis. F5 (0.75mg SA and 0.5mg HPMC) the optimized formulation showed a slow drug release of 96.10% up to 12 h. The best fit model for the drug release was Korsmeyer Peppas model which explained drug release on imbibition of water from surrounding by polymer matrix. Conclusion: The in situ gel prepared can ultimately provide prolonged release, enhance the bioavailability of the drug and increase the patient compliance due to development of a once in a day dosage form in comparison to multi dose of tablets therefore, can be considered as promising dosage form for increased therapeutic action.
Keywords: In situ gel; pH induced ion gelation; Sodium Alginate; CaCO3; Gastro; Retentive; Ropinirole Hydrochloride